'Schreibzeit' (marking time): an exploration of the permutational art and calendar calculations of Hanne Darboven. Issue 3 (2nd October 2021) - Wilson, J.
Abstract : Mathematical aspects of the work of the German conceptual artist, Hanne Darboven, are discussed, including the role of permutation, number representation and symmetry in her early works, and the use of a checksum calculation to record calendar dates in her later works. We analyse the multiple ways she represents the checksum calculations and explore the similarities and differences of her work with mathematics. We also suggest several mathematical questions arising from her work that would be interesting to explore in a discrete mathematics, number theory or liberal arts math classroom. GRAPHICAL ABSTRACT: UF0001